Learning Innovation of Islamic Education in Covid-19 Pandemic - Nursyahidin, Rahmad; Rohman, Arif; Febriyanti, Novi (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Nowadays, during the covid-19 pandemic, the development of educational technology has brought a significant influence and contribution to education in the world which urges learning innovations. This research used a qualitative method with a literature study approach. The results show that several innovations emerge as new breakthroughs so that education would no longer be monotonous and conventional. Those innovations are (1) Project Based Learning, (2) Daring Methods, (3) Luring Methods, (4) Integrated Curriculum, (5) Blended Learning. Behind the learning innovation there are also supporting opportunities through educational technology, including (1) Educational technology makes information in conveying material is easier to obtain, (2) Educational technology creates a very broad scope during the pandemic period, (3) Educational technology has a beneficial impact on education actors, (4) Technology can replace the position of educators with independent learning. However, there are also obstacles that pose challenges, including (1) Islamic sources (Al-Qur'an and Hadith) as a source of Islamic teachings, (2) Technology as a scientific product and (3) Human Resources as technology users for the success of e-learning.